2018
DOI: 10.1155/2018/6837404
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and/or Compost Applications Improve Soil Properties, Growth, and Yield of Maize Grown in Acidic Rainforest and Coastal Savannah Soils in Ghana

Abstract: Use of biochar for soil fertility improvement is gaining popularity due to its potential to improve soil quality, increase crop yield, and sequester carbon from the atmosphere-biosphere pool into the soil. A 40-day pot experiment was carried out to investigate the effects of corncob biochar and compost applied alone (at a rate of 2%, w/w) or in combination (1% of each, thus 1% compost + 1% biochar) on soil physicochemical properties, growth, and yield of maize on two soils of contrasting pH and texture collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
96
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(114 citation statements)
references
References 23 publications
16
96
1
1
Order By: Relevance
“…The increase in SOM was due to these amendments are endowed with a sizeable amount of total carbon within their structure with respectively 236 and 521 g kg -1 for compost and biochar, which underwent microbial decomposition, as well as could have sequestered atmospheric CO2. An upward trend in SOM due to compost addition was in agreement with (Cox et al, 2001;Mensah & Frimpong, 2018), while the one due to biochar addition was also in accordance with (Demisie et al, 2014;Mensah & Frimpong, 2018). Additionally, the contribution of organic materials in escalating SOM has been previously evidenced by Theobald et al (2018).…”
Section: Soil Organic Mattersupporting
confidence: 86%
“…The increase in SOM was due to these amendments are endowed with a sizeable amount of total carbon within their structure with respectively 236 and 521 g kg -1 for compost and biochar, which underwent microbial decomposition, as well as could have sequestered atmospheric CO2. An upward trend in SOM due to compost addition was in agreement with (Cox et al, 2001;Mensah & Frimpong, 2018), while the one due to biochar addition was also in accordance with (Demisie et al, 2014;Mensah & Frimpong, 2018). Additionally, the contribution of organic materials in escalating SOM has been previously evidenced by Theobald et al (2018).…”
Section: Soil Organic Mattersupporting
confidence: 86%
“…There are two aspects which make biochar amendment superior to other organic materials: the first is the high stability against decay, so that it can remain in soil for longer times providing long-term benefits to soil and the second is having more capability to retain the nutrients. Biochar amendment improves soil quality by increasing soil pH, moisture-holding capacity, cation-exchange capacity, and microbial flora [56].…”
Section: Biochar As a Soil Amendmentmentioning
confidence: 99%
“…The increase in pH with increase in dosage of biochar and fertilizer implies that application of biochar to agricultural soil in Ghana can help ameliorate the soil acidity problem identified by Dovana & Cassy [3]; Smith-Asante, [2]. In a similar study, Mensah and Frimpong [27] found that application of biochar with compost increased the soil pH. The increase in the pH could be attributed to the increase in available soil P due the presence of P in biochar [43] [44].…”
Section: Soil Physical Propertiesmentioning
confidence: 97%
“…Field-testing of biochar in Ghana has started albeit in a slow manner. Mensah and Frimpong [27] conducted an investigation on the effects of application of biochar (from corncobs) and compost on soil physicochemical properties, growth, and yield of maize on selected soils from the Rainforest and Coastal Savannah agroecological zones of Ghana. Amoakwah et al, [28] studied how biochar from corncobs alters soil water retention, air flow and derived soil structure indices in a tropical sandy loam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation